PENGUATAN KARAKTER POSITIF MELALUI MEDIA GAMBAR ILUSTRASI BERBASIS PROYEK PADA PEMBELAJARAN SENI RUPA - Wahyono, Bambang; Dewi Apriani Fr, Basukiyatno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a project-based instructional media in the form of illustrated images that focus on strengthening students' positive character within art education. The background of this study stems from the importance of character education emphasized in the Merdeka Curriculum and the continued lack of positive behaviors observed among students in schools. Weak character traits, such as lack of responsibility, poor collaboration, and low discipline, have been frequently observed among high school students, indicating a gap between curriculum intent and classroom reality. The research employed a 4D development model (Define, Design, Develop, Disseminate) with both qualitative and quantitative approaches to ensure a comprehensive evaluation of the media's development and impact. The subjects were 11th-grade students at SMA Negeri 2 Tegal, selected purposively based on preliminary needs analysis. Data collection techniques included observation, questionnaires, interviews, and documentation, while data analysis was carried out descriptively to present both numeric trends and narrative insight. The results indicate that the illustrated media developed was deemed feasible and effective in supporting art learning and in reinforcing values such as responsibility, cooperation, and discipline. Moreover, the project-based structure of the media enabled students to engage more actively, work collaboratively, and internalize character values through experiential learning. These findings suggest the need for the integration of project-based visual media into teaching strategies to holistically nurture students' character development in various subjects, especially those in the creative and expressive domains.